MMS application 'Motor Planet MMS' / Aiidill Johari - Aiidill, Johari (2005)
This report covers the overall specifications development of MOTOR PLANET MMS application. The main objective of this project is to develop a WAP sites that user can download images and animated GIF directly to their mobile phones. This proposal consists of 7 parts. The first part contains the project overview, objectives, scopes and limitation of project. It is then following by the second part; a through review of similar existing system is done earlier. This part is to better understanding regarding the project include requirement for developers, tools available strength and weakness , software such as scripting language and hardware. Chapter three will discuss the V-model where have been used to develop this application. Chapter four focused on the system design, how the architecture can be implemented in the project and data flow. The last part here will cover the implementations, application design and system testing. This system needs special development tools and languages such as Macromedia Dreamweaver, Microsoft Internet Information Server (IIS), Client/ Server three-tier System Architecture, Microsoft Access Database, ASP, WML, WML script, Windows XP Professional as development platform, Microsoft SQL Server 2000 and Cascading Style Sheet (CSS).